Substrate-binding glycine residues are major determinants for hydrolase and ligase activity of plant legumains - Hemu, Xinya (2023)
Peptide asparaginyl ligases (PALs) are Asn/Asp(Asx)-specific ligases that are useful for precision modifications of proteins and live-cell surfaces. PALs share high sequence and structural similarity to legumains, asparaginyl endopeptidases (AEPs) that primarily hydrolyze peptide bonds after Asx, thus making it challenging to identify PALs from AEPs. Previously, we showed that the substrate binding sequences flanking the catalytic site can strongly influence the enzymatic direction of a legumain and which we named as ligase activity determinants (LADs). Here, we show that two conserved substrate-binding Gly residues of LADs are critical, but negative determinants for ligase activity, based on a combined bioinformatics analysis of 1,500 plant legumains, mutagenesis, and functional study of 16 novel legumains, plus identification of seven new PALs. We also show that PALs are rare and AEPs are more common, accounting for about 1% and 88%, respectively. Our results suggest that specific glycine residues are molecular determinants to identify PALs and AEPs as two different legumain subfamilies.